1989
DOI: 10.1111/j.1751-1097.1989.tb04103.x
|View full text |Cite
|
Sign up to set email alerts
|

The Stepwise Biphotonic Photoionization of Chlorpromazine as Seen by Laser Flash Photolysis

Abstract: It is generally accepted that both promazine (PZ) and chlorpromazine (CPZ) photionize monophotonically to their respective cation radicals and the corresponding hydrated electrons. It is also supposed that this photoinization has a role in the phototoxic effects of these drugs. However, using laser flash photolysis, we have observed that photoionization of CPZ during S1 excitation (lambda greater than 300 nm) is a stepwise biphotonic process. In the case of PZ our flash photolysis results are less clearcut, bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0
1

Year Published

1996
1996
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 19 publications
2
27
0
1
Order By: Relevance
“…Interestingly, this product emits fluorescence and is not seen with exposures of higher concentrations of CPZ, nor is it observed with prolonged exposures of concentrations higher than 2 mg/mL. We interpret these findings to suggest that the rapid formation of products from CPZ at its lowest concentration yields a radical that is short lived and slightly more polar than CPZ and that it may represent a species that contains the sulfoxide previously suggested from flash photolysis of CPZ [32]. Monitoring the pH of the 2 mg/mL of CPZ during exposure indicated a rapid drop of 3 to 4 pH units within 5 minutes that was maintained for the duration of the two hour exposure (data not shown).…”
Section: Discussionmentioning
confidence: 60%
See 3 more Smart Citations
“…Interestingly, this product emits fluorescence and is not seen with exposures of higher concentrations of CPZ, nor is it observed with prolonged exposures of concentrations higher than 2 mg/mL. We interpret these findings to suggest that the rapid formation of products from CPZ at its lowest concentration yields a radical that is short lived and slightly more polar than CPZ and that it may represent a species that contains the sulfoxide previously suggested from flash photolysis of CPZ [32]. Monitoring the pH of the 2 mg/mL of CPZ during exposure indicated a rapid drop of 3 to 4 pH units within 5 minutes that was maintained for the duration of the two hour exposure (data not shown).…”
Section: Discussionmentioning
confidence: 60%
“…These studies showed that white light [28], incoherent UV light [31], coherent UV [48] and “flash photolysis” by a 266 nm laser [32], produced changes in structure of CPZ. The changes were perceived from indirect measurements that suggested the formation of radicals leading to the substitution at the sulfur atom (sulfoxides) and loss of the chloride at C-2 forming PZ.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus phenothiazines photoionization has been clearly demonstrated by several groups using transient absorption spectroscopy or EPR, but controversy remains over the mechanism of photoionization of these compounds. Motten et al [33], Buetner et al [34] and Hall et al [35] in contrast to the previous works proposed a wavelength-dependent photoionization of CPZ and promazine (PMZ) involving stepwise biphotonic photoionization through the triplet state at wavelength> 280 nm and monophotonic photoionization at wavelength <300 nm: this wavelength dependence suggest that the mechanism for cutaneous phototoxicity associated with clinical use of CPZ, which occur at solar wavelength >300 nm does not involve photoionization. More recently Garcia et al [36] in an elegant study using conditions where absorption by singlet or triplet excited states occur selectively have confirmed that photoionization occurs through biphotonic excitation for CPZ and PZ.…”
Section: Photophysical Characteristics Of Phenothiazinesmentioning
confidence: 90%